Environmental sustainability - Gonzalez, Elisa Gomez (Society Publishing., 2018)
This publication explores the challenges of presenting sustainability as a more actionable or practical concept and identifying approaches that might offer useful assistance in addressing the temporal and spatial representation of sustainability. The book provides a comprehensive framework and a practical tool to support the design process. This is a perfect text for students of natural and social sciences, development professionals and entrepreneurs seeking opportunities for ecologically sustainable businesses.